The Utility of Iris-pupillary Area Ratio as a Non-invasive Index of Stress in Primates - Lin, Annie; Maguire, Luc; Kilroy, David; Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Background: As pupillary diameter is exclusively regulated by the autonomic nervous sys- tem, the assessment of pupil size (pupillometry) provides an indirect measure of sympathetic nervous system activity and hence an estimation of the degree of stress in the patient. A reliable, objective and non-invasive measure of stress is useful in achieving optimal animal welfare standards, especially with exotic or zoo animals. Hence, we compared the iris-pupil- lary ratios in populations of wild and zoo monkeys to determine the suitability of using this ratio as a non-invasive index of stress. Materials and Methods: Digital photographs of wild (n=32) and zoo (n=19) monkeys were used to measure the iris-pupillary ratio of both eyes using NIH Image-J software. The data are represented as Mean ± SD and were compared us- ing unpaired t test with Welch’s correction. Results: The ratio of the iris-pupillary area in wild monkeys (17.03 ± 7.01) was significantly (p<0.0001) higher compared to zoo monkeys (8.80 ± 5.58). We observed a similar trend in the ratio of iris-pupillary perimeter (4.04 ± 1.22 Vs 2.91 ± 0.86). A lower ratio of iris-pupillary area or perimeter among zoo monkeys indicates pupillary dilation due to higher sympathetic activity and hence a higher level of stress. It is likely that the captive environment is a potential source of stress among zoo animals. We also evaluated the ratio of iris-pupillary mean grey values (1.58 ± 0.52 Vs 1.34 ± 1.09) and the ratio of iris- pupillary integrated density (27.69 ± 17.05 Vs 29.50 ± 10.95). These parameters were similar in the digital images of both wild and zoo monkeys, suggesting that the light conditions were similar in both groups. Conclusion: The data from this study support the utility of iris-pupillary area ratio as an objective, reliable and non-invasive index of degree of stress, which we be- lieve will be a useful tool in managing the animal welfare of exotic animal species.
Keywords: Iris-pupillary ratio; Sympathetic activity; Stress; Animal welfare; Digital imaging; Exotic animals; Primates